2011
DOI: 10.1029/2010jc006595
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions and bio-optical signature of a coccolithophorid bloom in the Patagonian shelf

Abstract: [1] In January 2008, a patch of high reflectance detected by ocean color satellite images was sampled during a cruise over the southern Argentinean continental shelf. High calcite concentrations (particulate inorganic carbon (PIC)) found at the patch were associated with dominance of the coccolithophorid Emiliania huxleyi. Relatively low chlorophyll concentrations (0.29 to 1.48 mg m −3 ) were found, but both particulate attenuation (0.27 to 1.15 m −1 ) and backscattering coefficients at 660 nm (0.003 to 0.042 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 58 publications
6
48
1
2
Order By: Relevance
“…Importantly, the rate of individual coccolith production by an E. huxleyi cell will be determined by both its cellular calcification rate and its coccolith calcite content: a cell calcifying at a rate of 0.3 pmol C d −1 (average value from (Tyrrell & Merico 2004, Signorini et al 2006, Garcia et al 2011. The Patagonian Shelf is a complex hydrographic regime, where warm low-nutrient subtropical waters from the north mix with cold highnutrient waters from the Southern Ocean (Painter et al 2010, Garcia et al 2011 ) was present along the southern portion of the shelf (Fig. 2, Table 2), with waters elevated in calcite being carried north via the northern flow of the Falklands (Malvinas) current (Painter al.…”
Section: Abstract: Emiliania Huxleyi · Calcification · Patagonian Shmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the rate of individual coccolith production by an E. huxleyi cell will be determined by both its cellular calcification rate and its coccolith calcite content: a cell calcifying at a rate of 0.3 pmol C d −1 (average value from (Tyrrell & Merico 2004, Signorini et al 2006, Garcia et al 2011. The Patagonian Shelf is a complex hydrographic regime, where warm low-nutrient subtropical waters from the north mix with cold highnutrient waters from the Southern Ocean (Painter et al 2010, Garcia et al 2011 ) was present along the southern portion of the shelf (Fig. 2, Table 2), with waters elevated in calcite being carried north via the northern flow of the Falklands (Malvinas) current (Painter al.…”
Section: Abstract: Emiliania Huxleyi · Calcification · Patagonian Shmentioning
confidence: 99%
“…A temperature versus salinity plot for the full-depth CTD data (Fig. 4) showed the presence of several water masses along the Patagonian Shelf (see also Painter et al 2010, Garcia et al 2011, so that each sampling station could be classified within a water mass ( (Stns 040,047,072,078,090,116,128,142) with salinities between 33.6 and 33.9.…”
Section: General Oceanographymentioning
confidence: 99%
See 1 more Smart Citation
“…after June in nAtl and for the austral summer in sAtl (except for the year 2010). Considering that these regions are characterized as high activity areas of coccolithophore blooms (Holligan et al, 1993;Raitsos et al, 2006;Painter et al, 2010;Garcia et al, 2011), along with the fact that the large reflectance from coccolithophore-rich surface waters affects the performance of the standard chl a algorithms (Gordon et al, 1988;Ackleson et al, 1988;Balch et al, 1989;Balch, 2004), the overestimation of coccolithophores observed in Fig. 7 may be attributed to the proposed underestimation of chl a during the coccolithophore blooms for the GlobColour data set.…”
Section: Time Series Of Biological and Geophysical Parametersmentioning
confidence: 94%
“…To monitor the development of coccolithophore blooms, regions of high occurrence were selected based on the following procedure: first, a global distribution of coccolithophores, mapped by Brown and Yoder (1994a) and Brown (1995) was considered; secondly, eight years of global distribution of PIC (from MODIS-Aqua) were monitored as monthly composites; and finally coccolithophore field studies were analyzed (Brown and Podesta, 1997;Balch et al, 1991;Holligan et al, 1993;Garcia et al, 2011;Raitsos et al, 2006;Painter et al, 2010;Burns, 1977;Tilburg et al, 2002). Based on these pre-investigations, three regions have been selected (Fig.…”
Section: Initial Tests and Selection Of Regionsmentioning
confidence: 99%